Relish : an adventure in food, style, and everyday fun - Oz, Daphne. (William Morrow, an imprint of HarperCollinsPublishers, 2013)
"Daphne Oz a co-host on the hit daytime talk show The Chew, bestselling author of THE DORM ROOM DIET, and Dr. Mehmet Oz's daughter offers simple, practical advice on living your best life right now"--